JUMPA Vol. 4 No. 1, Feb 2017 AKURASI FORWARD RATE SEBAGAI PENAKSIR FUTURE SPOT RATE KURS VALAS: AKURASI FORWARD RATE SEBAGAI PENAKSIR FUTURE SPOT RATE KURS VALAS - Mustanwir Zuhri Institut Keuangan Perbankan dan Informatika Asia Perbanas (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
The research objective was to analyze the accuracy or precision of the use of forward rate as predictors for the future spot rate of the Rupiah against the Japanese Yen (JPY) and US dollar (USD) during the observation period 2012-2015. Forward rate is determined by using the spot rate of foreign exchange rate and the difference in the level of inflation and interest rate between Indonesia and Japan and also between Indonesia and the United States. The method used is to test the average difference between the forward rate and the future spot rate by using criteria if the average forward rate did not differ significantly with the future spot rate, the forward rate is an appropriate estimator on future spot rate. The results showed that the forward rate for the currency USD is an appropriate future spot rate estimator by inserting the difference variable inflation and interest rate in the model while the forward rate of JPY is not an appropriate estimator.Recommendations can be given is that the relevant business decision makers should be better using the inflation and interest rate difference between Indonesia and the United States in determining the forward rate for the USD while JPY is not recommended. The second recommendation or suggestion is that scientists can further extend the research period and dividing the study period into segments (discrete) shorter